Przeoczony dyskurs, czyli rzecz o konstruktywizmie i (z)marnowanych szansach oceniania wczesnoszkolnego - Grażyna Szyling (Problemy Wczesnej Edukacji)
The aim of the paper is to reconstruct the (un)used chances which are generated for early education assessment by the constructive paradigm. In my reflections I take into account two complex and interpermeating perspectives: the premises of educational theory and educational practice. I order the area of reflection thus created by means of the assessment categories present in the language of practicalised didactics and colloquial assessment discourses. The analysis of declared assumptions, tacitly adopted or overlooked in various concepts and solutions, leads to the conclusion that in early education assessment constructivism is not so much an overlooked discourse, but distorted by normative convictions and educational practices.